Vitreomacular Interface Abnormalities in Myopic Foveoschisis: Correlation With Morphological Features and Outcome of Vitrectomy - Fang, Dong; Wang, Li; Chen, Lu; Liang, Jia; Li, Kunke; Mao, Xingxing; Xie, Ting; Zhang, Shaochong (Frontiers in Medicine, 2022)
Purpose. To compare the morphologic characteristics and response to surgery of myopic foveoschisis (MF) with different patterns of vitreomacular interface abnormalities (VMIAs). Methods. In this observational case series, 158 eyes of 121 MF patients with epiretinal membrane (ERM) or vitreomacular traction (VMT) based on optical coherence tomography (OCT) were enrolled. All eyes were divided into two groups by the pattern of VMIAs: ERM and VMT group. Sixty-one eyes underwent pars plana vitrectomy (PPV) and were followed up for at least 6 months. The morphologic characteristics based on OCT and the surgical outcome were evaluated. Outcome. ERM and VMT were found in 47.47% and 52.53% of the cases, respectively. A higher rate of foveal detachment (61.4% vs. 26.7%; P < 0.001) and a higher rate of outer lamellar macular hole (45.8% vs. 21.3%; P = 0.001) were detected in the eyes with VMT compared with those with ERM. In contrast, a lower rate of inner lamellar macular hole (28.9% vs. 60.0%; P = 0.001) was detected in the eyes with VMT compared with those with ERM. The disruption of the external limiting membrane (ELM) was more common in the eyes with VMT than in those with ERM (45.8% vs. 21.3%; P = 0.001). PPV was performed in 61 eyes with a mean follow-up time of 23.55±19.92 months. After surgery, anatomical resolution was achieved in 51 eyes (83.6%). At the final visit, the mean central foveal thickness (CFT) decreased significantly from 547.83 μm to 118.74 μm, and the mean LogMAR BCVA improved significantly from 0.92 to 0.57. The VMT group was associated with a higher proportion of eyes with visual acuity improvement postoperatively (P = 0.02) and had more decrease of CFT (P = 0.007) compared with the ERM group. Conclusion. In eyes with MF, outer retinal lesions occurred more frequently in eyes with VMT, whereas inner retinal lesions occurred more frequently in eyes with ERM. Tangential force generated by ERM may act as a causative factor for the inner retinal lesions in MF, and inward-directed force resulting from VMT may act as a causative factor for outer retinal lesions in MF.